Intranasal Nanotransferosomal Gel for Quercetin Brain Targeting: I. Optimization, Characterization, Brain Localization, and Cytotoxic Studies - Mohammed H. Elkomy; Randa Mohammed Zaki; Omar A. Alsaidan; Mohammed Elmowafy; Ameeduzzafar Zafar; Khaled Shalaby; Mohamed A. Abdelgawad; Fatma I. Abo El-Ela; Mostafa E. Rateb; Ibrahim A. Naguib; Hussein M. Eid (Pharmaceutics, 2023)
Numerous neurological disorders have a pathophysiology that involves an increase in free radical production in the brain. Quercetin (QER) is a nutraceutical compound that shields the brain against oxidative stress-induced neurodegeneration. Nonetheless, its low oral bioavailability diminishes brain delivery. Therefore, the current study aimed to formulate QER-loaded transferosomal nanovesicles (QER-TFS) in situ gel for QER brain delivery via the intranasal route. This study explored the impacts of lipid amount, edge activator (EA) amount, and EA type on vesicle diameter, entrapment, and cumulative amount permeated through nasal mucosa (24 h). The optimum formulation was then integrated into a thermosensitive gel after its physical and morphological characteristics were assessed. Assessments of the optimized QER-TFS showed nanometric vesicles (171.4 ± 3.4 nm) with spherical shapes and adequate entrapment efficiency (78.2 ± 2.8%). The results of short-term stability and high zeta potential value (−32.6 ± 1.4 mV) of QER-TFS confirmed their high stability. Compared with the QER solution, the optimized QER-TFS in situ gel formulation exhibited sustained release behavior and augmented nasal mucosa permeability. CT scanning of rat brains demonstrated the buildup of gold nanoparticles (GNPs) in the brains of all treatment groups, with a greater level of GNPs noted in the rats given the transferosomal gel. Additionally, in vitro studies on PCS-200-014 cells revealed minimal cytotoxicity of QER-TFS in situ gel. Based on these results, the developed transferosomal nanovesicles may be a suitable nanocarrier for QER brain targeting through the intranasal route.